AGE OF Eucalyptus urograndis PLANTATIONS AND OCCURRENCE OF PEST INSECTS - Joana Gabriela Freitas Andrade; Verissimo Gibran Mendes Sá; Sara Lodi; Bruno Spacek Godoy (Revista Árvore)
ABSTRACT Eucalyptus species are originally from Australia and its plantations is the major forestry activity in Brazil. The Myrtaceae family is widely represented in Brazil, enabling native insects to migrate to Eucalyptus plants. Native herbivorous insects may adapt to the species planted in monoculture with low availability of their natural host plants and natural enemies. Within this context, the differential occurrence pattern of eleven insect pests of Lepidoptera, Coleoptera and Hemiptera orders, from 450 Eucalyptus stands of different ages recorded in 2002 to 2010 in eastern State of Minas Gerais, Brazil was evaluated. Bayesian inference was used for data analyses in hypothesis testing. The probability of occurrence of pest species was estimated using a linear multinomial model, relating their occurrence with the Eucalyptus stand age. Pest occurrence in Eucalyptus stands were linked to plant age, with younger ones being more susceptible to phytophagous insects. That association with chronological plant age may be associated with the resource exploration strategy of each group of pest insects. Thus, Eucalyptus forest management should be adapted to the temporally differential use of the stands by pest species, providing more efficient control strategies.